Reaktualisasi Pemaknaan Zakat Sebagai Pembersih Harta (Studi Kritis atas Pemaknaan Surat at-Taubat ayat 103) - Taufik Setyaudin (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2019)
Zakat, in this case regarded to Zakat al-Mal (wealth Zakat) as one among Five Pillars of Islam, is misled to the wrong perception as the worship refers to wealth purification. If we care to step back on its historical aspect, particularly those written in the Asbab an-Nuzul Al Qur’an of Surah at-Tawbah verse 103 –which is commonly well-known as ‘the verse of zakat’, we shall understand that the real meaning extracted from the verse is all about soul rather than wealth purification –which is, unfortunately, still flourished among the society’s mind. This misleading interpretation will surely create inappropriate ways of gaining properties by ignoring the status of halal/haram it may takes; people assume that after zakat, their wealthis purified. Here is also an evidence of obscuring the meaning of sadaqah as the tool of purifying sins the people commit, as instance, purifying the wealth raised by corruption or other criminal behaviors. The study is importance to conduct to help revisiting the basic function of zakat as a contribution to the equalization of welfare in every level of society. To this case, therefore, this study will use the historical approach to revise the essential meaning of zakat assoul purification by optimizing the book of Asbab an-Nuzul and the linkage of verses on Zakat. This essay is also equipped with the perspectives of experts of exegesis and expert of Fiqh on Zakat, particularly those related to the Zakat al-Mal.